A review of fog computing and machine learning: Concepts, applications, challenges, and open issues - Abdulkareem K.H.; Mohammed M.A.; Gunasekaran S.S.; Al-Mhiqani M.N.; Mutlag A.A.; Mostafa S.A.; Ali N.S.; Ibrahim D.A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Applications; Computer graphics; Decision making; Energy utilization; Fog; Green computing; Internet of things; Learning algorithms; Learning systems; Machine learning; Natural language processing systems; Speech recognition; Computing applications; Computing paradigm; Internet of Things (IOT); NAtural language processing; Neuromorphic computing; Research challenges; Research domains; Resource management; Fog computing